Supervisi Akademik Internal Guru TK Dengan Pendekatan Kolaboratif - Windarta, Libri Rizka Puri (WISDOM: Jurnal Pendidikan Anak Usia Dini, 2021)
The principals have their own authority to carry out internal supervision and choose the type of approach used in schools according to the characteristics of the institution. The benefits of internal academic supervision are to improve teacher professional competence and teacher techniques in the learning process. The research was conducted at ABA Sumberadi Kindergarten which has 7 teachers, conducted in December. The purpose of this research is to get a real picture of institutions that use a collaborative approach in academic supervision. This type of research is qualitative, research subjects are principals and teachers. Techniques for collecting interview data and documents, interviews were conducted directly by the principal and teachers by meeting at school. The research data analysis technique used descriptive qualitative analysis techniques by analyzing the data obtained from interviews and then processed and presented with narration. The findings of this study are the collaborative approach is the approach chosen by schools because it is considered more effective for institutional improvement and principals are more flexible in exploring obstacles that arise in the learning process.